KESEJAHTERAAN PSIKOLOGI ISTRI PERTAMA DALAM PERNIKAHAN POLIGAMI - Mawardah, Mutia; Rostanti, Siti Rohma Rostanti (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2018)
This study aims to know the welfare of the psychology of the first wife in polygamy marriage. What factors affect the psychological welfare of a first wife in polygamy, as well as what causes a wife in polygamy. This research uses qualitative research design as well as using and using a case study approach to be able to know the welfare of the psychology of the first wife in polygamy marriage. In this study, researchers used 7 people sources, 2 people as the subject of research, 4 people as informant know of each subject and 1 person as the informant of the perpetrator. The results of this study found that the cause of both subjects in polygamy were among men's riches, consideration of the nobility, and religious considerations. The subjects in this study also had different psychological welfare. The first subject has six-dimensional welfare psychology, while the second subject has only four of the six dimensions of psychological wellbeing. Every dimension that belongs to the subject is also influenced by factors such as religious and social support factors